PENGARUH METODE LATIHAN INTERVAL TERHADAP HASIL LARI 60 METER PADA PESERTA DIDIK KELAS V SD NEGERI 009 SIMPANG KUBU KECAMATAN KAMPAR KABUPATEN KAMPAR - alfian alfian (Universitas Syiah Kuala, 2023)
The purpose of the study. This research is motivated by the results of the 60 meter run conducted by the fifth grade students of SD Negeri 009 Simpang Kubu, Kampar District, Kampar Regency, which is not optimal and not appropriate in its implementation.Materials and methods.. Research Methods This research uses a pre-experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was simple random sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test.Results. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. The results of the study based on the statistical output of